PROTECTION OF PERSONAL DATA ON WHATSAPP IN THE PERSPECTIVE OF LAW NO. 19 OF 2016 ABOUT ELECTRONIC INFORMATION AND TRANSACTION (ITE) - Kirana, Yanti; Basyarudin (Awang Long Law Review, 2021)
Rapid technological progress in the field of communication has led to many innovations and new ideas, ideas that aim to make the process of human communication more effective. One innovation that facilitates the communication process is a cell phone or commonly abbreviated with the word mobile. The emergence of various smartphones such as Blackberry, Android, Iphone, Windows Phone and Symbian S60 is an example of technological sophistication in the form of cellphones. From the various types of smartphones that are available, many of them offer advanced application features such as the instant messenger service application, "WhatsApp Messenger". WhatsApp Messenger as a communication tool is used by all groups, including teenagers who are inseparable from the need for communication. This study uses a survey method, a questionnaire that used in survey activities with a focus on the use of ICT by households and individuals is a direct survey of households and individuals to conduct face-to-face interviews (respondents) with respondents using a list of questions (questionnaire). Keywords: Psychology and Professional Ethics. An empirical juridical approach is carried out with field research aimed at the application of criminal procedural law in criminal cases. Normative juridical approach or library approach. The data that has been obtained is processed through the editing process, such as the process of checking and re-checking the data from the journal results and compiled systematically and in detail for further presentations in the journal " PROTECTION OF PERSONAL DATA ON WHATSAPP IN THE PERSPECTIVE OF LAW NO. 19 OF 2016 ABOUT ELECTRONIC INFORMATION AND TRANSACTION ( ITE ) ". Based on the identification of the above problems, the problem formulation can be raised as follows: 1. How to use Whatsapp Messenger as a medium of interpersonal and community communication? 2. Are there law sanctions for someone who prints a talk on the WhatsApp screen group? That people actively search for certain media and certain content to produce certain satisfaction (results). that individuals or communities use media and mass media content to meet certain needs that can provide satisfaction for them. so that individuals or audiences have greater freedom to choose and determine media content and media that can provide satisfaction, compared to the power of the media to influence them.